1985
DOI: 10.1136/bjsm.19.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Grip strength and forearm straps in tennis elbow.

Abstract: Twenty-seven patients who presented with tennis elbow had their grip strengths measured without a forearm strap, with an elastic strap and with an inelastic strap. Of these 85% displayed an increased pain-free grip strength with one or both straps. The increase in pain-free grip strength was statistically significant for both types of strap (p < 0.001) and the results showed no consistent difference between them. The possible mode of action is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 6 publications
(3 reference statements)
0
5
1
Order By: Relevance
“…The significant differences in grip strength are comparable with the report by Vicenzino et al in which the authors reported that using a diamond tape could significantly increase grip strength in patients with tennis elbow ( 23 ). Although, in our study, the mean increase in grip strength was not similar to Burton’s report ( 24 ), a major difference between studies was the test position used to measure grip strength. The current study and that by Wadsworth ( 25 ) and Wuori ( 26 ) tested grip strength in 90° of flexion, whereas the others had the elbow in extension (23).…”
Section: Discussioncontrasting
confidence: 99%
“…The significant differences in grip strength are comparable with the report by Vicenzino et al in which the authors reported that using a diamond tape could significantly increase grip strength in patients with tennis elbow ( 23 ). Although, in our study, the mean increase in grip strength was not similar to Burton’s report ( 24 ), a major difference between studies was the test position used to measure grip strength. The current study and that by Wadsworth ( 25 ) and Wuori ( 26 ) tested grip strength in 90° of flexion, whereas the others had the elbow in extension (23).…”
Section: Discussioncontrasting
confidence: 99%
“…17 A similar upper-limb position has been used in previous research. 4,29,28,35 Participants were instructed to smoothly increase their grip force, and cease squeezing at the onset of lateral epicondylar pain while maintaining the upper limb in the standardized test position.…”
Section: Outcome Measures (Dependent Variables)mentioning
confidence: 99%
“…The strong correlation between level of disability and deficits in pain-free grip strength testing, 20 along with its responsiveness to change and high reliability, has facilitated its use as an indicator of physical impairment and dysfunction not only in the laboratory but also in the clinical setting. 4,26,25 Stratford and Levy 25 have shown the pain-free grip strength test to be a more sensitive instrument of change than the maximum grip strength test.…”
mentioning
confidence: 99%
“…In contrast with the studies of Kainien (1988) and Priest et al, (1980), in a self report study of tennis players, Gruchow and Pelletier (1979) found that a forearm brace was not effective in reducing pain. Burton (1985) found that pain free grip strength in subjects with tennis elbow was greater while wearing a below elbow band, keither elastic or inelastic) than without one, in 70% of subjects. Like the previous self-report studies, a number of variables were not controlled or reported.…”
Section: Below-elbovv Splintsmentioning
confidence: 95%
“…Following an extensive literature search no studies were found in which the long-term treatment effect of wearing tennis elbow splints was carefully measured. Various potentially advantageous biomechanical effects have been demonstrated in subjects with lateral epicondylitis, during a short time of actual wearing of below elbow lateral counterforce splints (Burton, 1985;Froimson, 1971;Wadsworth, Nielsen, Bums, Krull & Thompson, 1989). The designs of these studies did not allow for control of variables such as splint design, concurrent treatments and wearing regimes, nor did they have objective outcome measures of the treatment.…”
Section: Résumémentioning
confidence: 99%